Using wearable microtechnology to measure precision of pre-determined change of direction incidents of varying angles. - Balloch, A. S.; Meghji, M.; Habibi, D.; Hart, N. H.; Weber, J.; Newton, R. U. (Journal of Australian Strength and Conditioning, 2016)
Cumulative change of direction incidents can elicit high levels of musculoskeletal and neuromuscular fatigue which may alter mechanical loading on lower-body joints and subsequently reduce mechanical efficiency, underpinning an increased risk of injury. Inertial sensors have previously shown the capability to accurately identify and differentiate between a variety of sports-specific movements. Therefore, the aim of this study was to determine whether an accurate and reliable algorithm could be developed to calculate the precise angle from a range of pre-determined change of direction incidents.